Dose–response relationships of rabeprazole 5, 10, 20, and 40 mg once daily on suppression of gastric acid secretion through the night in healthy Japanese individuals with different CYP2C19 genotypes - Hayato, Seiichi; Hasegawa, Setsuo; Hojo, Seiichiro; Okawa, Hiroki; Abe, Hiroaki; Sugisaki, Nobuyuki; Munesue, Masahiro; Horai, Yukio; Ohnishi, Akihiro (European journal of clinical pharmacology, 2012)
Purpose This study was designed to investigate the antisecretory activity of rabeprazole administered once daily in doses of 5, 10, 20, and 40 mg and different cytochrome P450 2C19 (CYP2C19) genotypes on gastric pH in healthy individuals. Additional objectives were delineating the nighttime from the daytime effect and determining the relationships between the pharmacokinetics and pharmacodynamics of rabeprazole. Methods Eight individuals of each of the three genotypes of CYP2C19—homozygous extensive metabolizers (homo-EMs), heterozygous EMs (hetero-EMs), and poor metabolizers (PMs)—were recruited. Twenty-four individuals received a once-daily dose, with dosing interval 24 h of 5, 10, 20, or 40 mg rabeprazole for 5 days in a 4-period crossover fashion. Twenty-four-hour intragastric pH and plasma rabeprazole concentrations were determined on day 5. Results A dose-dependent increase in median pH and in pH 4 holding time was observed across all CYP2C19 genotypes. When rabeprazole was increased from 20 mg to 40 mg, the differences and 95% confidence intervals (CIs) of nighttime pH 4 holding time between 40 mg and 20 mg in homo-EMs, hetero-EMs, and PMs were 8.0% (−5.0% − 21.0%), 28.7% (15.7% − 41.6%), and 16.9% (3.9% − 29.9%), respectively. The relationship between the area under the plasma concentration-time curve up to the last time point at which rabeprazole was quantifiable (AUC 0-t ) and the pH 4 holding time could be described using a sigmoid maximum effect (E max ) model. Conclusions Our data demonstrate that increasing rabeprazole dose up to 40 mg once daily results in an increasing pharmacodynamic effect, which is most apparent for the control of nocturnal gastric acid secretion.